The effectiveness of the fixed drug combinations of lisinopril with meldonium and of enalapril with nitrendipine in arterial hypertension patients with cognitive impairment - Shmanko, O. V. (Journal of Education, Health and Sport, 2015)
Shmanko O. V. Ефективність фіксованих комбінацій лізиноприлу з мельдонієм та еналаприлу з нітрендипіном у хворих на артеріальну гіпертензію з когнітивними розладами = The effectiveness of the fixed drug combinations of lisinopril with meldonium and of enalapril with nitrendipine in arterial hypertension patients with cognitive impairment. Journal of Education, Health and Sport. 2015;5(10):327-339. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34077 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A327-339 https://pbn.nauka.gov.pl/works/670816 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 31.10.2015. УДК 616.12- 008.331.1-06:616.89-008.46-085.214.32/.225.2 ЕФЕКТИВНІСТЬ ФІКСОВАНИХ КОМБІНАЦІЙ ЛІЗИНОПРИЛУ З МЕЛЬДОНІЄМ ТА ЕНАЛАПРИЛУ З НІТРЕНДИПІНОМ У ХВОРИХ НА АРТЕРІАЛЬНУ ГІПЕРТЕНЗІЮ З КОГНІТИВНИМИ РОЗЛАДАМИ THE EFFECTIVENESS OF THE FIXED DRUG COMBINATIONS OF LISINOPRIL WITH MELDONIUM AND OF ENALAPRIL WITH NITRENDIPINE IN ARTERIAL HYPERTENSION PATIENTS WITH COGNITIVE IMPAIRMENT О. В. Шманько O. V. Shmanko ДВНЗ "Тернопільський державний медичний університет ім. І.Я. Горбачевського МОЗ України" Тернопіль, Україна Ternopil State Medical University Ternopil, Ukraine Summary The results of the comparative assessment of the effects of fixed drug combinations of lisinopril with meldonium and of enalapril with nitrendipine on cognitive disorders in patients with arterial hypertension are presented. It was found that the use of fixed drug combinations of lisinopril with meldonium and of enalapril with nitrendipine in hypertensive patients with cognitive impairment could be considered as having cerebro-protective effect, based on neuropsychological examination (MMSE, MOCA), on evaluation of the quality of life (SF-12) and on patients’ own subjective state reports, which gives us an indication to use fixed drug combination of enalapril with nitrendipine for moderate cognitive impairment, longer duration of disease and higher degree of arterial hypertension, and fixed drug combination of lisinopril with meldonium for mild cognitive impairment in patients with arterial hypertension. Keywords: arterial hypertension, cognitive impairment, lisinopril, meldonium, enalapril, nitrendipine. Резюме Представлені результати ефективності фіксованих комбінацій лізиноприлу з мельдонієм та еналаприлу з нітрендипіном у хворих на артеріальну гіпертензію з когнітивними розладами. Встановлено, що фіксовані комбінації лізиноприлу з мельдонієм та еналаприлу з нітрендипіном за нейропсихологічними тестами (MMSE,MOCA), оцінкою якості життя (SF- 12), суб’єктивним станом хворих на артеріальну гіпертензію можна розцінювати як засоби, що мають церебропротективний ефект, що дозволяє застосовувати еналаприл з нітрендипіном при помірних когнітивних розладах, більшій тривалості і вищому ступені артеріальної гіпертензії, а лізиноприл з мельдонієм при легких когнітивних порушеннях у хворих на артеріальну гіпертензію. Ключові слова: артеріальна гіпертензія, когнітивні розлади, лізиноприл, мельдоній, еналаприл, нітрендипін.